Doutor, você me escuta, você me vê? Uma abordagem da aceitação e uso da teleconsulta no Brasil - Soares , Roberto Antonio Rodrigues (2023)
A new experience in the relationship between patients and doctors in Brazil has emerged after the release of Teleconsultation from March of 2020. The activity has been discussed and has implemented in other countries since the late 20th century and early 2000s and it has been supported by WHO. However, previous studies have mostly focused on providing care in remote areas, moving patients, as well as improving the efficiency of care for the population, based on studies of a technical-scientific approach in the fields of Medicine and Information Technology. The need for social distancing and the entry of new consumers into the Teleconsultation modality in Brazil have become a challenge and new opportunities for both health professionals and private health plans in seeking patient’s experience and approval. This dissertation intends to investigate the enablers and detractor factors that collaborate in the acceptance and experience of Teleconsultation services in Brazil, using the qualitative research approach. At first, we carried out an exploratory research with the collection of secondary data through literature and visits to websites on the internet (main health plans, government agencies and Reclame Aqui social website) for a better understand of the theme and the existing scenario. Subsequently, we carried out a descriptive approach in the collection of primary data through in-depth individual interviews, using semi-structured scripts with users of Teleconsultation in Brazil. Finally, the content analysis of the findings collaborates in the presentation of a proposal framework with the main factors that may affect Teleconsultation patients’ journey, as well provides indicators for future researches in the Teleconsultation and creates a technological product for health professionals.